Detection of vertebral insufficiency fractures on 18F-FDG PET/CT following radiation therapy for oesophageal cancer - George Ashton, MBChB, BMedSci; Karan Bir Singh, MBBS, SCHP; Eamonn J Mayo, MBBS; Stephen R Thompson, MBBS, FRANZCR, PhD; Eva A Wegner, BMed, FRACP, FAANMS, MHM (Radiology Case Reports, 2025)
A 62-year-old man and 70-year-old woman with oesophageal cancer treated with chemoradiotherapy underwent 18F-FDG PET/CT (FDG-PET/CT) for assessment of suspected thoracic vertebral metastases. Each was found to have a thoracic vertebral fracture with mild linear FDG uptake. The location of these fractures within the radiotherapy field was in keeping with insufficiency fractures post-therapy. The diagnosis and the exclusion of metastases was achieved by FDG-PET/CT, as demonstrated by the discussed cases.